Retrospective study of impact of social factor in pediatric trauma at teaching hospital of Vindhya region of India - Singh, Lal Mani; Yadalwar, Vinod (International Surgery Journal, 2018)
Background: Pediatric trauma i.e. Fall, RTA, burn and other type of trauma is primarily seen in neglected young children, these children’s are unattended to and unprotected at home due to overburdened parents in nuclear family busy with various household and outdoor jobs. In present study aims to analyse the different aspect of social factors that related to trauma in pediatric age group. Methods: The present retrospective study was carried out in 367 patients of the age group <1-15 years during the period 2015-2016.A detailed history taking (from parents/relatives/children) and examination was done and all patients were assessed with regards to their age, sex, mode of trauma/injury, type of injury, site of trauma, place of trauma, and mortality, type of family, number of family members, parents job to create data. The children were classified according to age group. Modes of trauma were divided in groups; the types of injury were divided into subgroups. The places of trauma were divided into the following: Home, road, farm, school/playground or park and others. Results: Out of total 36.96% of cases were pediatric trauma, (127) belongs to the age group1-5 years. In the less than one year age group burns was the major cause of trauma (47.05%). Boys was dominating (63.21%) over girls (36.78%) on whole but girls were at an increased risk of burn injuries (32.59%) than boys (14.66%) most of the pediatric trauma occurred when the child was unaccompanied (59.9%) as compared to accompanied with elders (40.1%)unaccompanied male was more prone to injury than an accompanied. Head injury was (47.41%) and incidence of fall was (53.45%). Mortality rate was maximum (70.6%) in age group less than one year followed by 11-15 years age group (17.0%). mortality rate was higher in female15.67% as compare male 12.9. Conclusions: The study shows that needs to focus on maintain data analysis to make a policy for management of pediatric trauma, incidence of all type trauma can be reduced by awareness of society members, a large number of public illiterate and unaware even when literate to take care of children’s. Needs to make special awareness program to give a massage to society make well designed home and playground don’t make children’s free to play in road or other places except to play ground.